Analisis Faktor Ketidaklengkapan Pengisian Catatan Perkembangan Pasien Terintegrasi (CPPT) Perawat pada Rawat Inap terhadap Policy Brief RSUD Balaraja Tahun 2025 - Siti Mulyatul Rohmah (Jurnal Manajemen dan Administrasi Rumah Sakit Indonesia (MARSI), 2026)
The Integrated Patient Progress Notes (CPPT) are a crucial component of medical records because they support continuity of care, ensure patient safety, and improve the quality of hospital services. This study was conducted to identify various factors contributing to the incomplete filling of CPPT by nurses in the inpatient ward of Balaraja Regional General Hospital, which will then form the basis for the preparation of a policy brief related to improving the quality of nursing documentation. This study used a qualitative approach with in-depth interviews with nurses, ward heads, medical record unit heads, and hospital management, as well as document observation. The data were analyzed using the Miles and Huberman interactive model. The results of this study indicate that the main factors contributing to incompleteness are high workloads, time constraints, lack of training, weak supervision, and the absence of strict sanctions. The implementation of electronic medical records (EMR) has improved readability and consistency, but has not yet fully improved the content of records such as SOAP and nursing plans. The conclusion of this study emphasizes the importance of policy interventions based on training, supervision, and optimization of electronic systems to improve the quality of CPPT documentation. Keywords: Integrated Patient Progress Notes (CPPT), Incomplete Documentation, Inpatient Nurses, Policy Brief, Balaraja Regional General Hospital.